2021
DOI: 10.32327/ijmess/10.2-3.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Exchange Rate Fluctuations on Nigeria’s Economic Performance: An Autoregressive Distributed Lag (ARDL) Approach

Abstract: This study examined the effects of persistent exchange rate fluctuations on Nigeria's economic performance. It was motivated by the quest to ascertain why concerted efforts of the monetary authorities in Nigeria to pursue internal and external balances yielded little or no positive results in recent periods. The study employed the autoregressive distribution lag (ARDL) technique to test the short-run and long-run effects of exchange rate fluctuations on economic growth using annual time series data from 1986 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This current study revealed that exchange rate depreciation, inflation, and monetary policy rates have negative impacts on real GDP in both short and long-run. This revelation is consistent with extant empirical findings (Adewuyi & Akpokodje, 2013;Alagidede & Ibrahim, 2017;Iheanachor & Ozegbe, 2021). Exchange rate has been volatile because of continued dependence on oil for revenue and foreign exchange earnings (Ndu-Okereke & Nwachukwu, 2017).…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 3 more Smart Citations
“…This current study revealed that exchange rate depreciation, inflation, and monetary policy rates have negative impacts on real GDP in both short and long-run. This revelation is consistent with extant empirical findings (Adewuyi & Akpokodje, 2013;Alagidede & Ibrahim, 2017;Iheanachor & Ozegbe, 2021). Exchange rate has been volatile because of continued dependence on oil for revenue and foreign exchange earnings (Ndu-Okereke & Nwachukwu, 2017).…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Flexible exchange rate regime is a critical reflection of the free market economic structure (Iheanachor & Ozegbe, 2021). In such a structure, the exchange rate oscillates frequently and such oscillations have a direct or indirect impact on the economy which can be observed through the macroeconomic performances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations